2009
DOI: 10.1094/mpmi-22-9-1128
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Diversity of CLAVATA3/ESR (CLE)-Like Genes from the Potato Cyst Nematode Globodera rostochiensis

Abstract: Plant CLAVATA3/ESR-related (CLE) peptides have diverse roles in plant growth and development. Here, we report the isolation and functional characterization of five new CLE genes from the potato cyst nematode Globodera rostochiensis. Unlike typical plant CLE peptides that contain a single CLE motif, four of the five Gr-CLE genes encode CLE proteins with multiple CLE motifs. These Gr-CLE genes were found to be specifically expressed within the dorsal esophageal gland cell of nematode parasitic stages, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
149
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(152 citation statements)
references
References 58 publications
1
149
0
Order By: Relevance
“…It has long been known that cyst nematodes secrete peptides that are structural and functional mimics of plant CLAVATA3/ENDOSPERM SURROUNDING REGION-related (CLE) peptides (Wang et al, 2001(Wang et al, , 2005Gao et al, 2003;Lu et al, 2009), with the latter being peptide hormones required for meristem maintenance and vascular differentiation (Fiers et al, 2007). The nematode CLE effectors are required for virulence (Patel et al, 2008), apparently by stimulating both the CLV2 and the CLV1 pathways (Replogle et al, 2011(Replogle et al, , 2013.…”
Section: Manipulation Of Rlp and Rlk Signaling By Pathogen Effectorsmentioning
confidence: 99%
“…It has long been known that cyst nematodes secrete peptides that are structural and functional mimics of plant CLAVATA3/ENDOSPERM SURROUNDING REGION-related (CLE) peptides (Wang et al, 2001(Wang et al, , 2005Gao et al, 2003;Lu et al, 2009), with the latter being peptide hormones required for meristem maintenance and vascular differentiation (Fiers et al, 2007). The nematode CLE effectors are required for virulence (Patel et al, 2008), apparently by stimulating both the CLV2 and the CLV1 pathways (Replogle et al, 2011(Replogle et al, , 2013.…”
Section: Manipulation Of Rlp and Rlk Signaling By Pathogen Effectorsmentioning
confidence: 99%
“…The CLE-like effectors seem to be unique to cyst nematodes, as no other CLElike effectors have been identified outside cyst nematodes so far. The function of cyst nematode CLE-like effectors in mimicking endogenous plant peptides is supported by experimental data showing that overexpression of nematode CLE-like effectors in Arabidopsis produced a WUSCHEL phenotype (premature termination of shoot and floral meristems) similar to that of plant CLE overexpression (Wang et al, 2005Lu et al, 2009). Nematode CLE-like effectors were also able to complement the Arabidopsis clavata3-2 (clv3-2) null mutant (Lu et al, 2009;Wang et al, 2010).…”
Section: Mimicry Of Host Factorsmentioning
confidence: 94%
“…The function of cyst nematode CLE-like effectors in mimicking endogenous plant peptides is supported by experimental data showing that overexpression of nematode CLE-like effectors in Arabidopsis produced a WUSCHEL phenotype (premature termination of shoot and floral meristems) similar to that of plant CLE overexpression (Wang et al, 2005Lu et al, 2009). Nematode CLE-like effectors were also able to complement the Arabidopsis clavata3-2 (clv3-2) null mutant (Lu et al, 2009;Wang et al, 2010). Genetic and molecular analyses indicated that plant CLE peptides are perceived by various receptor-like kinases (RLKs) to mediate the downstream signaling essential for correct stem cell fate (Guo et al, 2010(Guo et al, , 2011Kinoshita et al, 2010).…”
Section: Mimicry Of Host Factorsmentioning
confidence: 94%
“…These cell wall degrading enzymes help the infective J2 nematodes to migrate through the plant roots by softening the cell wall. The effector proteins include CLAVATA3 (CLV3) /ESR (CLE) -like (Wang et al, 2005;Patel et al, 2008;Lu et al, 2009;Wang et al, 2010a;Wang et al, 2010b), SPRY domain-containing (SPRYSEC) effector proteins (Huang et al, 2006;Rehman et al, 2009;Sacco et al, 2009;Postma et al, 2012), Mi-EFF1 (Jaouannet et al, 2012), calreticulin Mi-CRT (Jaubert et al, 2002;Jaubert et al, 2005;Jaouannet et al, 2013), and Hs19C07 (Lee et al, 2011). These proteins are involved in plant-nematode compatible interactions by suppressing the defense mechanisms of host plants in some cases.…”
Section: Parasitomes/secretomes and Parasitism Genes Of The Nematodesmentioning
confidence: 99%